The relative neglect of agriculture in Mozambique - Jo\~ao Z. Carrilho; Ines A. Ferreira; Rui N. Ribeiro; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
This paper explores agricultural performance of Mozambique, its institutional weaknesses, and the underlying factors that underpin an unsatisfactory performance during many decades. We point to the role of systemic political instability and violence combined with challenges to state legitimacy. Regional divides and lack of market integration continue to influence in a critical and all-encompassing manner. Finally, the way in which the interests of the elite and the influence of donors have affected progress in the agriculture sector suggests the need for concerted reorientation in existing strategies, policies, and priorities. This is reinforced by future challenges, including the extractive industry; population growth and internal migration; national and international markets; climate change; and COVID-19. We highlight the need to place the future of agriculture in Mozambique within a long-term perspective, focusing on the adoption and stabilization of an institutional framework aimed at increasing agricultural productivity and preserving the environment.
Keywords: Q01; Q15; Q16; Q18; 330; agriculture; environment; institutions; agricultural policy; productivity